Low Temperature Synthesis of Biodiesel via Heterogeneous Potassium-Alumina Catalyst - Az Zahra, Aghietyas Choirun; Cengko, Geraldi; Hijran, Azra; Rizkiana, Jenny (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Indonesia, one of the world's largest producers of crude palm oil (CPO), is aiming to achieve a renewable energy mix target of 23% by 2025 through the implementation of a B35 policy, blending diesel with fatty acid methyl ester (FAME) derived from CPO transesterification. Traditionally, homogeneous catalysts are used in this process, but their sensitivity to free fatty acids reduces biodiesel yield. Therefore, heterogeneous catalysts are being developed to overcome this issue, contributing to sustainable biodiesel production. However, certain heterogeneous catalysts require high temperature, more methanol, longer reaction times, necessitating the exploration of more optimal catalyst options. This study introduces an approach by exploring the use of heterogeneous K2O/g-Al2O3 catalysts in biodiesel production from RBDPO under low-temperature conditions (40 °C), a significant reduction from the commonly operated temperature of near the boiling point of methanol at 60 °C. Utilizing KI and KNO3 as precursors, the effect on different catalyst precursor, temperatures and reaction time were examined. It was found that temperature has the highest effect on conversion. The transesterification process yielded biodiesel with FAME levels ranging from 95.84% to 98.17%, meeting the Indonesian National Standard (SNI 7182:2015) for biodiesel quality. The findings indicate that both KI and KNO3 precursors result in highly active K2O/g-Al2O3 catalysts, achieving high conversion at 40 °C within a 1-hour reaction time, thus demonstrating their effectiveness in low-temperature biodiesel synthesis. This low-temperature process has the potential to significantly reduce energy consumption in industrial biodiesel production. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).